If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 15 = -3 Reorder the terms: 15 + 9x = -3 Solving 15 + 9x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 9x = -3 + -15 Combine like terms: 15 + -15 = 0 0 + 9x = -3 + -15 9x = -3 + -15 Combine like terms: -3 + -15 = -18 9x = -18 Divide each side by '9'. x = -2 Simplifying x = -2
| X^2+11x+10=o | | x/9-8=3 | | 0.029x+4=0.034x | | 0.2x-1=6 | | 3x-6(x+6)=-66 | | -3(6+7)x=171 | | 5x^2+42=2x^2+117 | | 6x^2+9x-8=0 | | 7(1x+3)=105 | | A+B+15=45 | | 7x+2(4x+8)=4 | | 7+10n=37 | | -8+6(3g+6)= | | 180=y-4 | | -3x-8y+20y=5x+19 | | 4x^2-2x-120=0 | | 11x-4=11+2 | | 4(-5x-6)=-4 | | x/5+17=20 | | 2(7-4x)=-74 | | 9y^2+27y+14= | | 7(-7x+8)=-483 | | 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 | | 5+(-24)= | | 2.5d+7.75=4+3.25d | | 6(x+3)-4(x-3)= | | 3w^2(w^2+3)=8+7w^2 |